2020
DOI: 10.1002/adhm.202000647
|View full text |Cite|
|
Sign up to set email alerts
|

Unnatural Amino‐Acid‐Based Star‐Shaped Poly(l‐Ornithine)s as Emerging Long‐Term and Biofilm‐Disrupting Antimicrobial Peptides to Treat Pseudomonas aeruginosa‐Infected Burn Wounds

Abstract: Peptide-based antimicrobial materials are recognized as promising alternatives to antibiotics to circumvent the emergence of antibiotic-resistant bacteria or to combat multiple resistant bacteria by targeting the bacterial cell membrane. The components and conformations of antimicrobial peptides are extensively explored to achieve broad-spectrum and effective antimicrobial activity. Here, star-shaped antimicrobial polypeptides are fabricated by employing homologs of poly(l-lysine)s (i.e., poly(l-ornithine)s, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 39 publications
2
31
0
1
Order By: Relevance
“…24 Catabolic states such as burns affect the ornithine level in tissues in the body. 25 In the present study, it was found that the level of ornithine was increased in the follow-up of both the dead and surviving patients. The authors could not explain the relationship of ornithine level with both survival and mortality.…”
supporting
confidence: 55%
“…24 Catabolic states such as burns affect the ornithine level in tissues in the body. 25 In the present study, it was found that the level of ornithine was increased in the follow-up of both the dead and surviving patients. The authors could not explain the relationship of ornithine level with both survival and mortality.…”
supporting
confidence: 55%
“…Furthermore, SMAMPs exhibit significant advantages over natural AMPs, such as enhanced antimicrobial activity, flexible framework for chemical modification, improved physicochemical stability, and better compatibility with drug-delivery methodology 53 . Recently, unnatural antibacterial peptidomimetics of various backbone structure have emerged with promising potential, such as poly( α -amino acid)s 54 , 55 , 56 , 57 , poly( β -amino acid)s 58 , 59 , polymethacrylate 60 , 61 , 62 , polymethacrylamide 63 , 64 , poly(2-oxazoline) 65 , 66 , polycarbonates 67 , 68 , polynorbornene 69 , 70 , peptidopolysaccharides 41 , 71 , poly(isobutylene- alt-N -alkyl maleimide) 72 , 73 , 74 , β -peptides 75 , peptoids, and AApeptides 76 , 77 , 78 , 79 , 80 . The antibacterial performance of these MDPs is primarily affected by factors, such as amphiphilicity, charge, cationic chemical functionality, molecular weight, sequence, biodegradability, and subunit stereoisomerism.…”
Section: Mdps and Their Mechanisms Of Actionmentioning
confidence: 99%
“…More recently, cationic star-shaped antimicrobials have been developed as unique molecular scaffolds that provide a high charge density for binding anionic bacterial bilayers 82 , 119 , 120 , 121 , 122 , 123 . Cai's group 55 , 56 , 57 highlighted that enhancing the cationic charge density of SMAMPs by transforming their backbone from linear to star-shaped could facilitate their electrostatic binding affinity toward bacterial cell membranes and give them a unique membrane perturbation capability ( Fig. 4 E).…”
Section: Mdps and Their Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some lipopeptides in solution could behave in a similar manner to antimicrobial peptides, since they can form micelles to reach high local concentrations with bactericidal effect (Chongsiriwatana et al 2011). The use of a few amino acids including Ornithine linked to the fatty acids provide stability, maintaining the antimicrobial activity at low concentrations (Meir et al 2017, Pan et al 2020.…”
Section: Introductionmentioning
confidence: 99%